Development of a model for analyzing the impact of communication on productivity - Narváez Martínez, Andrés Guillermo
This review article explores the impact of organizational communication on business productivity. Through the review of several recent studies, key variables were identified, including the transmission of emotions in messages, message orientation, clarity of objectives, employee inclusion in decision-making, frequency of interactions, network communication topology, and management of techno-stressors. The findings suggest that efficient, well-designed communication tailored to the needs of the work environment can significantly enhance employee productivity and performance.